2010
DOI: 10.1002/app.31777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poly(methyl methacrylate) addition on the dielectric and energy storage properties of poly(vinylidene fluoride)

Abstract: Poly(methyl methacrylate) (PMMA) was introduced into poly(vinylidene fluoride) (PVDF) via a solution blending process, and a series of PVDF/PMMA blends were obtained in an effort to reduce the energy loss of pure PVDF. The effects of the composition and thermal treatment on the properties of the polymer blends were carefully studied. The results show that the introduction of PMMA led to a lower crystallinity and a smaller crystal size of PVDF for its dilution effect. As a result, the dielectric constant and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 61 publications
3
62
0
Order By: Relevance
“…The DSC analysis results show the general reduction in crystallinity, indicating that the absolute ratio of alpha and beta deceases while the percent of gamma rising. Similar conclusion was drawn by Zhicheng Zhang for P(VDF TrFE) polymer blends [16].…”
Section: Structure Characterization Of Biaxially Oriented P (Vdf Hfp)supporting
confidence: 85%
See 1 more Smart Citation
“…The DSC analysis results show the general reduction in crystallinity, indicating that the absolute ratio of alpha and beta deceases while the percent of gamma rising. Similar conclusion was drawn by Zhicheng Zhang for P(VDF TrFE) polymer blends [16].…”
Section: Structure Characterization Of Biaxially Oriented P (Vdf Hfp)supporting
confidence: 85%
“…The peaks at 840 and 1278 cm -1 are assigned to the β phase of P(VDF HFP) [14][15][16] which overlap with the absorption of PMMA, so that they can not be used to quantify the content change of beta phase. Figure 2 shows the XRD spectra of biaxial oriented P(VDF HFP)/PMMA blend films.…”
Section: Structure Characterization Of Biaxially Oriented P (Vdf Hfp)mentioning
confidence: 99%
“…Although the same energy density or even high energy density has been achieved in other reported PMMA modified ferroelectric polymer systems like PVDF/PMMA blend, P(VDF‐TrFE)/PMMA blend, P(VDF‐TrFE‐CTFE)‐grafted‐PMMA, and so on, the charge‐discharge efficiency is usually below 90%. The high efficiency in this work is among the highest lever compared with literature results shown in Table .…”
Section: Resultsmentioning
confidence: 63%
“…The crystalline phase of PVDF could not be changed by PMMA but could be changed by the addition of P2VP [21,22]. Besides, Meng et al [23] found that with the increase of PMMA content, the phase of PVDF in the polymer blends could transfer from a-PVDF to b-PVDF. For the study of PVDF/SAN/PMMA ternary blend, it was found that the inclusion of PMMA could confine the movement of PVDF chains and reduce the lamella thickness and the degree of crystallinity [24].…”
Section: Introductionmentioning
confidence: 97%